2022
DOI: 10.1007/s13555-022-00874-z
|View full text |Cite
|
Sign up to set email alerts
|

An Intelligent Diagnostic Model for Melasma Based on Deep Learning and Multimode Image Input

Abstract: Introduction:The diagnosis of melasma is often based on the naked-eye judgment of physicians. However, this is a challenge for inexperienced physicians and non-professionals, and incorrect treatment might have serious consequences. Therefore, it is important to develop an accurate method for melasma diagnosis. The objective of this study is to develop and validate an intelligent diagnostic system based on deep learning for melasma images. Methods: A total of 8010 images in the VISIA system, comprising 4005 ima… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 36 publications
0
6
0
Order By: Relevance
“…The Swin transformer is a new model of computer vision proposed in 2021 with a wide applicability for tasks including image segmentation, image recovery, and image reconstruction [144,145]. Currently, only a limited number of studies have reported the use of this model for medical images [146][147][148]. The Swin transformer, through its hierarchical structure and selfattentive mechanism, has shown powerful feature extraction and modeling capabilities in medical image processing, providing potential opportunities for improvement and innovation in medical image analysis and diagnosis [149].…”
Section: Actively Explore Innovative Models and Methodsmentioning
confidence: 99%
“…The Swin transformer is a new model of computer vision proposed in 2021 with a wide applicability for tasks including image segmentation, image recovery, and image reconstruction [144,145]. Currently, only a limited number of studies have reported the use of this model for medical images [146][147][148]. The Swin transformer, through its hierarchical structure and selfattentive mechanism, has shown powerful feature extraction and modeling capabilities in medical image processing, providing potential opportunities for improvement and innovation in medical image analysis and diagnosis [149].…”
Section: Actively Explore Innovative Models and Methodsmentioning
confidence: 99%
“…This presents promising opportunities for innovation in medical image analysis and diagnosis. Currently, there have been limited studies reporting the utilization of Swin Transformer in the context of medical images 51 53 . As far as we are aware, our study stands out as one of the relatively few instances where the Swin Transformer has been applied to the analysis of dermoscopic images.…”
Section: Discussionmentioning
confidence: 99%
“…(2) cosmetics usage and makeup tutorial [14,41,68,84], (3) skin physical assessment [13,33,88], (4) skin condition diagnosis [27,45,82,87], (5) treatment & skincare products recommendation [1,32,55,66], (6) treatment outcome prediction [6,53,63], etc. The above work mainly involves skin imaging technology, which makes contributions to skin diagnosis and treatment by using artificial intelligence to understand various types of image information.…”
Section: Computer-aided Skincare Tools In Hci Communitymentioning
confidence: 99%